ESL learners’ use of language learning strategies: an exploratory study / Ahmad Faiz Sapuan - Sapuan, Ahmad Faiz (2011)
This study investigated the ESL learners language learning strategies use of 60 Form Four of a secondary school relation to language proficiency and stream. Purposely, it examined the type and frequency of language learning strategies used by the high, average and low language proficiency students and streams and the differences between them. In addition, the study attempted to discover the relationship between the ESL learners’ proficiency and stream of the language learning strategies namely Compensation Strategies, Memory Strategies, Cognitive Strategies, Social Strategies, Affective Strategies and Metacognitive Strategies. The research design is a cross sectional survey research, which used the Strategy Inventory Language Learning (SILL) questionnaire developed by Oxford (1990). The Independence Variable of the study is the frequency of language learning strategies used by different level of proficiency of students. On the other hand, the Dependence Variable of the study is the six language learning strategies as measured by SILL. The level of proficiencies of students will affect the frequency of students using the language learning strategies in their learning. Data obtained from the questionnaire were analyzed using One-Way ANOVA, independent T-Test, Pearson’s Correlation Coefficient and Tukey HSD. This study also provides pedagogical implications and suggestions for future research.